Case report: Focal segmental glomerulosclerosis in a pediatric atypical progeroid syndrome - Seoyun Jang; Yo Han Ahn; Yo Han Ahn; Yo Han Ahn; Jung Min Ko; Jung Min Ko; Jung Min Ko; Jae Sung Ko; Sojung Lim; Hee Gyung Kang; Hee Gyung Kang; Hee Gyung Kang (Frontiers Media S.A., 2022)
Atypical progeroid syndrome (APS) is a rare type of progeroid syndrome mainly caused by heterozygous missense mutations in the LMNA (MIM 150330) gene. APS has heterogeneous clinical manifestations, and its kidney manifestations, particularly in children, are rarely documented. Here, we report the first pediatric case of APS with focal segmental glomerulosclerosis (FSGS). A 10-year-old boy with progeroid features was referred to the nephrology clinic because of hyperuricemia. He had dark skin, protruding eyes, and beaked nose and was very thin, suggesting lipodystrophy. He had been treated for recurrent urinary tract infection during infancy, and liver biopsy for persisting hepatitis showed steatohepatitis. He also had hypertrophic cardiomyopathy (HCMP) with mitral and tricuspid valve regurgitation. Genetic studies were performed considering his multisystem symptoms, and he was diagnosed as having APS according to exome sequencing findings (c.898G > C, p.Asp300His of LMNA). During the first visit to the nephrology clinic, he had minimal proteinuria (urine protein/creatinine ratio of 0.23 mg/mg), which worsened during follow-up. In three years, his urine protein/creatinine ratio and N-acetyl-b-D-glucosaminidase/creatinine ratio increased to 1.52 and 18.7, respectively. The kidney biopsy result was consistent with findings of FSGS, peri-hilar type, showing segmental sclerosis of 1 (5%) glomerulus out of 21 glomeruli. An angiotensin receptor blocker was added to manage his proteinuria. This is the first pediatric report of FSGS in an APS patient with confirmed LMNA defect, who manifested progeroid features, lipodystrophy, HCMP with heart valve dysfunction, and steatohepatitis. Our case suggests that screening for proteinuric nephropathy is essential for managing APS patients since childhood.